Electrical cardiac injuries: current concepts and management. (20th April 2017) - Waldmann, Victor; Narayanan, Kumar; Combes, Nicolas; Jost, Daniel; Jouven, Xavier; Marijon, Eloi
Abstract: Electrical injuries are a commonly encountered hazard in both the home and workplace. However, clinicians are often uncomfortable when faced with the patient who presents with an electric shock due to sparse literature and lack of systematic recommendations on this topic. Electrical injuries can range from minor skin burns to life threatening internal organ damage. A thorough clinical assessment to ascertain the path of current through the body and possible internal injury is essential. The main concern in an apparently stable individual after an electric shock is the potential for delayed occurrence of cardiac arrhythmias which will require monitoring in the intensive care setting. While it may be reasonable to discharge home from the emergency room selected patients with low voltage injuries, absence of syncope and a normal ECG, others may require monitoring for at least 24 h. Public education and increasing workplace as well as home safety measures are key steps in prevention. The present review summarizes current knowledge in pathophysiology, manifestations and management of electrical injuries, with specific focus on cardiac effects.